A MULTI-DIMENSIONAL SERVICE DELIVERY AMONG MOBILE NETWORK PROVIDERS IN GHANA: A CASE OF CUSTOMER SATISFACTION - Asiedu, Michael; Sarfo, Jacob Owusu (European Scientific Journal, ESJ, 2013)
The aim of the study was to identify the dimensions of mobile telecommunication services in Ghana as well as to develop a model to identify consumer satisfaction. The research was a non-experimental, explorative, quantitative study. Structured questionnaire was used to collect data from a sample of hundred (300) participants from the University of Ghana.The result showed that the majority of the respondents were satisfied with the overall mobile service offered by their service providers. From the results, call quality was found to be the most important determinant of consumer satisfaction with mobile telecommunication services (β = 0.276, t= 5.729, P< 0.001).This was followed by Network charges (β =0.209, t= 4.344, P< 0.01). In conclusion, the study results suggests that customer niche is a very peculiar one, with several unique characteristic with regards to their demographic and preferences and therefore should be targeted with the kind marketing activities that is likely to interest them